Possible Role of Endothelial-Derived Cellular and Exosomal-miRNAs in Lipid-Mediated Diabetic Retinopathy: Microarray Studies - Khaled Elmasry; Samar Habib; Inas Helwa; Mariam Lotfy Khaled; Ahmed S. Ibrahim; Amany Tawfik; Mohamed Al-Shabrawey (Cells)
Diabetic retinopathy (DR) is a salient cause of blindness worldwide. There is still an immense need to understand the pathophysiology of DR to discover better diagnostic and therapeutic modalities. Human retinal endothelial cells (HRECs) were treated with 15-HETE or D-glucose, then miRNAs were isolated, and a microarray was performed. MirWALK 2 and Ingenuity Pathway Analysis (IPA) were used to analyze the microarray results. Exosomal miRNAs from 15-HETE-treated HRECs were isolated, microarrayed, and then imported into IPA for further analysis. The microarray results showed that 15-HETE downregulated 343 miRNAs and upregulated 297 miRNAs in HRECs. High glucose treatment induced a differential expression of HREC-miRNAs where 185 miRNAs were downregulated and 244 were upregulated. Comparing the impact of 15-HETE versus DG or diabetic mouse retina elaborated commonly changing miRNAs. Pathway and target analysis for miRNAs changed in 15-HETE-treated HRECs revealed multiple targets and pathways that may be involved in 15-HETE-induced retinal endothelial dysfunction. The HREC-exosomal miRNAs were differentially expressed after 15-HETE treatment, with 34 miRNAs downregulated and 45 miRNAs upregulated, impacting different cellular pathways. Here, we show that 15-HETE induces various changes in the cellular and exosomal miRNA profile of HRECs, highlighting the importance of targeting the 12/15 lipoxygenase pathway in DR.